Comparison of Radiographic Parameters Used to Assess Haglund Deformities in an Asian Population: A Case–Control Study - Fu Yuen Thong; Tanawat Vaseenon; Theenesh Theyvan; Pawee Chalidapong; Jirawat Saengsin (Journal of Foot and Ankle Surgery (Asia Pacific))
Introduction: Posterior heel pain is a frequently observed manifestation of foot and ankle discomfort. The condition is primarily attributed to many types of soft tissue disorders, such as bursitis and tendinopathy, as well as bone abnormalities such as posterosuperior deformity and posterior calcaneal spur. The management of these diverse entities should be delineated based on the underlying etiology of pain. Lateral calcaneus radiography is employed to detect bone pathology associated with this condition. Nevertheless, the predictive efficacy of all bone and spur measuring parameters remains equivocal. The objective was to assess the predictive efficacy of a novel radiographic test, known as bone prominence measurement (BPM), in comparison to existing methods. Materials and methods: A total of 184 individuals were categorized into two groups based on the presence or absence of posterior heel pain: symptomatic and asymptomatic. The weight-bearing lateral radiography measurements of the X/Y ratio, Fowler–Philip angle (FPA), Heneghan–Pavlov parallel pitch line (HPPPL), Chauveaux–Liet angle (CLA), and BPM were examined using a Chi-squared test. Results: There was no statistically significant difference between the two symptomatic groups in terms of X/Y ratio, FPA, and CLA. The HPPPL exhibited a notable disparity in the symptomatic group but demonstrated low specificity and positive predictive value (PPV). The 5 mm bony prominence’s BPM parameter demonstrated a PPV of 90.4%, a sensitivity of 90.4%, and a specificity of 90.0%. A statistically significant difference was seen in BPM with a p-value of 0.001. Conclusion: BPM is a useful marker for confirming the presence of symptomatic posterior heel pain. The size of the posterior heel spur may be associated with improper tension on the Achilles tendon and the alleviation of symptoms following surgical removal.